2007
DOI: 10.1007/s10693-007-0021-4
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Rating Agency Reputation on Local Government Bond Yields

Abstract: G12, G24, Split ratings, municipal bonds, rating agencies, reputation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 15 publications
0
12
1
Order By: Relevance
“…Consistent with prior literature, we identify whether the splits are the result of Moody's Investor Services (Moody's) assigning a higher rating versus Standard and Poor's (S&P's) assigning a higher rating with the omitted comparison category being joint ratings. Existing empirical evidence shows that the market reacts differently to split ratings as investors do not weight ratings equally (Cantor, Packer, and Cole ; Hauck and Neyer ; Livingston and Zhou ; Livingston et al, ) and that S&P is more likely to assign a higher rating (or positive outlook) relative to Moody's (Allen and Dudney ; Farmer, ; Kioko, Johnson, and Moldogaziev ). Negotiated sales are often used for more complex debt instruments.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with prior literature, we identify whether the splits are the result of Moody's Investor Services (Moody's) assigning a higher rating versus Standard and Poor's (S&P's) assigning a higher rating with the omitted comparison category being joint ratings. Existing empirical evidence shows that the market reacts differently to split ratings as investors do not weight ratings equally (Cantor, Packer, and Cole ; Hauck and Neyer ; Livingston and Zhou ; Livingston et al, ) and that S&P is more likely to assign a higher rating (or positive outlook) relative to Moody's (Allen and Dudney ; Farmer, ; Kioko, Johnson, and Moldogaziev ). Negotiated sales are often used for more complex debt instruments.…”
Section: Methodsmentioning
confidence: 99%
“…The literature on differences among credit rating agencies has shown that the type of criteria and the weighting of each criteria considered in a rating varies by agency (Cluff and Farnham 1984; Jewell and Livingston ; Moon and Stotsky ,; Livingston, Jie, and Zhou ; Allen and Dudney ). While S&P and Moody's both claim to use the same general categories of variables in determining ratings, Cluff and Farnham (1984) find that S&P tends to place more emphasis on economic base and demographic factors while Moody's weighs debt burden and other financial measures more heavily.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…This activity develops a reputation and regard among investors that ensures client firms continue to seek the services of the agency. However, in the earliest stages, credit rating agencies have no reputation with which to attract client firms (Allen and Dudney 2008). This situation could result in awarding inappropriately high credit ratings to build a base of client firms and may help explain the extremely disproportional distribution of ratings.…”
Section: Corporate Bondsmentioning
confidence: 99%